Hubungan antara kebiasaan merokok, minum kopi, dan status gizi dengan hipertensi pada karyawan office boy Universitas Pembangunan Nasional “Veteran” Jakarta tahun 2018 - Muhammad Ikhsan Amar; Ismu Wahid Ramadhani; Avliya Quratul Marjan (Fakultas Kedokteran Universitas Gadjah Mada, 2019)
Hypertension is one of the high incidence diseases in Indonesia. Hypertension is a condition where blood vessels have high blood pressure (systolic blood pressure ≥ 140 mmHg or diastolic blood pressure ≥ 90 mmHg). The prevalence of hypertension in adulthood was 23.3% in Indonesia. The purpose of this study was to determine the relationship of smoking habits, coffee drinking, and nutritional status with hypertension in office boy at Universitas Pembangunan Nasional “Veteran” Jakarta. The design of this study was cross sectional with 70 respondents sample in total that was taken by random sampling method. Data were analyzed by univariate and bivariate by Chi Square test. The results showed that there was a relationship between smoking habits (p = 0.005), drinking coffee (p value = 0,000), and nutritional status (p value = 0.005) with hypertension. The writer expected that if respondents could quit smoking, drinking coffee, and managed dietary habit it could increase the standard of health and decrease the incidence of hypertension.